Genetic Characterization and Population Connectedness of North American and European Dairy Goats - Teissier, Marc; Brito, Luiz F.; Schenkel, Flavio S.; Bruni, Guido; Fresi, Pancrazio; Bapst, Beat; Robert-Granie, Christèle; Larroque, Hélène (Frontiers in Genetics, 2022)
Genomic prediction of breeding values is routinely performed in several livestock breeding programs around the world. Nevertheless, the size of the training populations and the genetic structure of populations evaluated have, in many instances, limited the increase in the accuracy of genomic estimated breeding values. Combining phenotypic, pedigree, and genomic data from genetically-related populations can be a feasible strategy to overcome this limitation. However, the success of across-population genetic evaluations depends on the pedigree connectedness and genetic relationship among individuals from different populations. In this context, this study aimed to evaluate the genetic connectedness and population structure of Alpine and Saanen dairy goats from four countries involved in the European project SMARTER (Small Ruminants Breeding for Efficiency and Resilience), including Canada, France, Italy, and Switzerland. These analyses are paramount for assessing the potential feasibility of an across-country genomic evaluation in dairy goats. Approximately 9,855 genotyped individuals (with 51% French genotyped animals) and 6,435,189 animals included in the pedigree files were available across all four populations. The pedigree analyses indicated that the exchange of breeding animals were mainly unilateral with flows from France to the other three countries. Italy has also imported breeding animals from Switzerland. Principal component analyses (PCA), admixture, and consistency of gametic phase revealed that French and Italian populations are more genetically related compared to the other dairy goat population pairs. Canadian dairy goats showed the largest within-breed heterogeneity as well as genetic differences with the European populations. The genetic diversity and population connectedness between the studied populations indicate that an international genomic evaluation may be more feasible, especially for French and Italian goats. Further studies will investigate the accuracy of genomic breeding values when combining the datasets from these four populations.